2021
DOI: 10.3390/ijerph18179077
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure of Lead and Cadmium Affect the Endometriosis?

Abstract: This study aimed to investigate the effects of blood lead levels (BLLs) and lead and cadmium exposure on endometriosis (EM). The study cohort consisted of female workers who underwent a lead-associated special medical examination between 1 January 2000 and 31 December 2004 (n = 26,542). The standard admission rate (SAR) and admission odds ratio (OR) for EM were calculated using the general population and noise-exposed groups, respectively, for the same period as the reference standards. The SAR for EM was 1.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Seven epidemiological studies have indicated associations between the exposure to selected metals and endometriosis (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ; Kim et al 2021 ; Silva et al 2013 , Yılmaz et al 2020 ). Studies mostly assess cadmium and lead exposure (six of them) (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ; Kim et al 2021 ; Silva et al 2013 ), copper (three of them) (Lai et al 2017 , Pollack et al 2013 , Yılmaz et al 2020 ), and mercury (four of them) (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ) exposure. Other metals such as nickel (Silva et al 2013 ; Yılmaz et al 2020 ), zinc (Lai et al 2017 ; Yılmaz et al 2020 ), manganese, iron (Lai et al 2017 ), aluminum (Yılmaz et al 2020 ), and chromium (Lai et al 2017 ; Pollack et al 2013 ) also have been studied in relation to endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven epidemiological studies have indicated associations between the exposure to selected metals and endometriosis (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ; Kim et al 2021 ; Silva et al 2013 , Yılmaz et al 2020 ). Studies mostly assess cadmium and lead exposure (six of them) (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ; Kim et al 2021 ; Silva et al 2013 ), copper (three of them) (Lai et al 2017 , Pollack et al 2013 , Yılmaz et al 2020 ), and mercury (four of them) (Zhang et al 2021 ; Lai et al 2017 ; Tanrikut et al 2014 ; Pollack et al 2013 ) exposure. Other metals such as nickel (Silva et al 2013 ; Yılmaz et al 2020 ), zinc (Lai et al 2017 ; Yılmaz et al 2020 ), manganese, iron (Lai et al 2017 ), aluminum (Yılmaz et al 2020 ), and chromium (Lai et al 2017 ; Pollack et al 2013 ) also have been studied in relation to endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 30 eligible articles included in the present systematic review, 16 articles focused on clinical studies investigating IVF outcomes (Table 1) (16, 21-35) while 14 articles focused on clinical studies that investigated reproductive concerns (Table 2) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigated the role of heavy metals and metalloids in infertility (41,47). The study by Tanrikut et al (40) revealed that Cd was found in 91% of women diagnosed with unexplained infertility against 34% of fertile women. Pb was found in 15% of women diagnosed with unexplained infertility and 3% of fertile women.…”
Section: Heavy Metals/metalloids and Reproductive Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed by Kim proved that co-exposure to cadmium as well as lead was associated with a higher incidence of hospitalization in patients suffering from endometriosis [ 90 ].…”
Section: Trace Elements and Endometriosismentioning
confidence: 99%